2020
DOI: 10.1186/s12934-020-01434-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomics of Phialemonium curvatum as an omnipotent fungus cultivated on crude palm oil versus glucose

Abstract: Background Sugars and triglycerides are common carbon sources for microorganisms. Nonetheless, a systematic comparative interpretation of metabolic changes upon vegetable oil or glucose as sole carbon source is still lacking. Selected fungi that can grow in acidic mineral salt media (MSM) with vegetable oil had been identified recently. Hence, this study aimed to investigate the overall metabolite changes of an omnipotent fungus and to reveal changes at central carbon metabolism corresponding to both carbon so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…Our study revealed that the effect of mixture treatment altered various metabolic pathways such as the citrate cycle, glyoxylate and dicarboxylate metabolism, and pyruvate metabolism. These pathways are linked to the synthesis of different secondary metabolites, which is consistent with a study [48]. Moreover, our metabolic study revealed the enhancement in various metabolites after the mixture treatment, which may be linked with the inhibition of lipid accumulation according to the previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed that the effect of mixture treatment altered various metabolic pathways such as the citrate cycle, glyoxylate and dicarboxylate metabolism, and pyruvate metabolism. These pathways are linked to the synthesis of different secondary metabolites, which is consistent with a study [48]. Moreover, our metabolic study revealed the enhancement in various metabolites after the mixture treatment, which may be linked with the inhibition of lipid accumulation according to the previous reports.…”
Section: Discussionsupporting
confidence: 92%
“…Untargeted LC‐MS was implemented to discover 10 new secondary metabolites produced by biosynthetic gene clusters in Fusarium graminearum (Adpressa et al., 2019). Metabolomes of Phialemonium curvatum strains were characterized after cultivation on crude palm oil vs. glucose using targeted LC‐MS and GC‐MS (Zamani et al., 2020). In the nematode‐trapping fungus Arthrobotrys oligospora , untargeted LC‐MS was performed on cell supernatants with over 8000 downregulated compounds detected in a mutant compared to a wild‐type strain (Bai et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these disadvantages were overcome by Phialemonium curvatum (Barig et␣al ., 2011) growing in 100‐litre plastic vessels in selective minimal medium. As reported recently (Barig et␣al ., 2017; Zamani et␣al ., 2020), different Aspergillus species as well as P. curvatum using crude palm oil as the sole source of carbon and energy were found to have an omnipotent anabolism.…”
Section: Introductionmentioning
confidence: 99%